Effect of Different Litter Materials on Broiler Performance and Quality of Litter - Cokorda Bagus Dharma Putra Mahardika; Bambang Hadisutanto; Herlyn Djunina (Fakultas Peternakan, Universitas Padjadjaran, 2021)
An effective bedding material must be compatible have high moisture absorption, lightweight, reduce feses contaminant, non-toxic and available. This research were conducted to investigate the effects of different litter materials on broiler performance (feed intake, average daily gain, body weight, feed conversion) and quality of litter (moisture, bulk density, temperature, pH). One hundred twenty eight broilers (Cobb CP-707 strain) were randomly distribute to different litter treatment: rice hull (control), peanut straw, corncob and corn straw. This experiments were conducted using a completely randomized design with four levels of treatment and four replications. Data were statistically analyzed using ANOVA with 5% significance level. A significance treatment (P≤0,05) will be continue analyzed to Duncan Multiple Range Test. The results showed that (1) litter materials (rice hull, peanut straw, corncob, and corn straw) had no significant influence (P>0,05) on feed intake, average daily gain, body weight and feed conversion. (2) rice hull, peanut straw, corncob and corn straw as a litter materials until 32-day treatment had significant influence (P≤0,05) on litter moisture but non significant on bulk density, temperature an pH of litters.